CURRENT THREATS TO MICROBIOLOGICAL FOOD SAFETY AND FOOD SAFETY REGULATION - MATЕYUK, OLESYA; YEFREMOVA, OLHA; MIRONOVA, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to the analysis of current problems of microbiological food safety in the context of globalization and technological progress. The main groups of microbiological pathogens (disease-causing bacteria; viruses; parasites; fungi and their toxins) are identified. The main factors that contribute to the emergence and spread of microbiological threats are considered, in particular: the emergence of new pathogens, the growth of antibiotic resistance, changes in production technologies and supply chains, as well as the impact of climate change.The article analyzes current trends in food safety regulation at the international and national levels: international and national regulations, standards and food safety management systems, such as HACCP, Codex Alimentarius, DSTU ISO 9001:2015, DSTU ISO 22000:2019. National legislation, sanitary norms and technical regulations that define food safety criteria are studied. The main types of microorganisms that can contaminate food products are analyzed: sanitary indicators, opportunistic pathogens, pathogenic microorganisms, spoilage microorganisms and probiotics. Particular attention is paid to the legal regulation of microbiological criteria for food safety in Ukraine, in particular, the norms for the presence of opportunistic and pathogenic microorganisms, pathogens of parasitic diseases and maximum permissible concentrations of mycotoxins in food raw materials and products of animal origin. The need for continuous improvement of control and regulatory systems to ensure food safety, the importance of systematic monitoring and control at all stages of the food chain, as well as the need to raise awareness and responsibility of food chain participants, including producers, distributors, retailers and consumers, are identified.
Keywords: microbiological safety; pathogenic microorganisms; food safety; food quality indicators; food quality standardization; maximum permissible concentration